Influence of egg weight on fertility and hatchability of backyard poultry varieties maintained under institutional farm conditions - PATRA, MANAS KUMAR; SANCHU, VIHIELE; NGULLIE, EBIBENI; HAJRA, D K; DEKA, BIDYUT C (The Indian Journal of Animal Sciences, 2016)
The study was conducted to investigate the effect of egg weight on fertility and hatchability in Vanaraja and Gramapriya chicken at a particular age. Depending on weight of eggs of Vanaraja (592) and Gramapriya (657) varieties, eggs were divided in Gr.1 (large, weight ≥65 g), Gr. 2 (medium, weight ≥52 to <65 g) and Gr. 3 (small, weight <52 g) and incubated in 3 batches. The size of egg had a significant effect on fertility, hatchability and chicks’ weight. The highest level of fertility was observed in medium sized eggs, followed by large and small sized eggs irrespective of variety. The hatchability on TES was higher in medium sized eggs as compared to small sized eggs. For large eggs, the weight was negatively correlated with hatchability on TES and on FES. In small sized eggs, egg weight was negatively correlated with hatchability on FES. The study indicated differential hatchability pattern in respect to egg weight and selection of medium to relatively higher sized egg, which would be beneficial for achieving better hatchability and future performance of the chicks of backyard poultry varieties.